EIF Private Equity Mid-Market Survey 2021: Market sentiment - Antonia Botsari; Kilian Kiefer; Frank Lang; Davide Legnani (European Investment Fund (EIF), 2021)
The EIF VC Survey, the EIF Private Equity Mid-Market Survey, and the EIF Business Angels Survey (the largest combined regular survey exercises among GPs and Business Angels on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2021 EIF PE Mid-Market Survey. The paper focuses on the market sentiment and the impact of COVID-19. The study looks at the current situation, developments in the recent past and expectations for the future. The main results are summarised and compared over time. The publication provides a valuable insight of the developments and the market situation in 2021, as well as an outlook for the near future.
Keywords: 330